Accelerated evolution of early angiosperms: Evidence from ranunculalean phylogeny by integrating living and fossil data. Issue 4 (15th April 2014) - Wang, Wei; Dilcher, David L.; Sun, Ge; Wang, Hong‐Shan; Chen, Zhi‐Duan
Abstract: The new discovery of angiosperm remains in the Jehol Biota of northeastern China contributes to our understanding of the origin and early evolution of flowering plants. The earliest eudicot genus with reproductive organs, Leefructus, was recently documented from the Lower Cretaceous Yixian Formation at 125.8–123.0 Ma, and was reconsidered to be close to the extant family Ranunculaceae based on gross morphology. However, this hypothesis has not been tested using a cladistic approach. To determine the possible allies of Leefructus within extant eudicots, we constructed a 66 morphological data matrix. Molecular and morphological analyses of extant Ranunculales combined with the fossil suggest that it has an affinity with the Ranunculaceae. The earliest fossil record of the eudicots is 127–125 Ma based on tricolpate pollen grains. Thus, we suggest a hypothesis that the basal eudicots might have experienced an accelerated evolution and diversification during the latest Barremian and earliest Aptian, leading to the stem groups of at least six extant families or lineages, 10–15 Myr earlier than currently documented. Angiosperms have undergone multiple uneven pulses of radiation since their origin. Many key character innovations occurred in different stages that could have triggered those radiations in concert with various biotic and abiotic factors.